“True to my own noble race”: Six Nations Women Teachers at Grand River in the early Twentieth Century - Norman, Alison (Ontario History)

(untitled) (The Ontario Historical Society, 2015)
While classrooms for Indigenous children across Canada were often taught by non-Indigenous men and women, at the Six Nations of Grand River, numerous Haudenosaunee women worked as teachers in the day schools and the residential school on the reserve. While very different from each other, Emily General, Julia Jamieson and Susan Hardie shared a passion for educating the young of their community, especially about Haudenosaunee culture and history, along with the provincial curriculum. They were community leaders, role models and activists with diverse goals, but they all served their community through teaching, and had a positive impact on the children they taught.